Something deeply hidden : quantum worlds and the emergence of spacetime - Carroll, Sean M., 1966- (Boston, Massachusetts : Dutton, an imprint of Penguin Random House, 2019)
"Caltech physicist and New York Times bestselling author Sean Carroll shows that there are multiple copies of you. And everyone else. Really. Something Deeply Hidden begins with the news that physics is in a crisis. Quantum mechanics underlies all of modern physics but major gaps in the theory have been ignored since 1927. Science popularizers keep telling us how weird it is, how contradictory, how impossible it is to understand. Academics discourage students from working on the "dead end" of quantum foundations. Putting his professional reputation on the line, Carroll says that crisis can now come to an end. We just have to accept that there is more than one of us in the universe. There are many, many Sean Carrolls. Many of every one of us The Many Worlds Theory of quantum behavior says that every time there is a quantum event, a world splits off with everything in it the same, except in that other world the quantum event didn't happen. As you read this, you are splitting into multiple copies of yourself thousands of times per second. Step-by-step in Carroll's uniquely lucid way, he sets out the major objections to this utterly mind-blowing notion until his case is inescapably established. The holy grail of modern physics is reconciling quantum mechanics with Einstein's general relativity -- his theory of curved spacetime. Carroll argues that our refusal to face up to the mysteries of quantum mechanics has blinded us, and that spacetime and gravity naturally emerge from a deeper reality called the wave function. No book for a popular audience has attempted to make this radical argument. We're on the threshold of a new way of understanding the cosmos." --
Part one : Spooky. What's going on : Looking at the quantum world -- The courageous formulation : Austere quantum mechanics -- Why would anybody think this? : How quantum mechanics came to be -- What cannot be known, because it does not exist : Uncertainty and complementarity -- Entangled up in blue : Wave functions of many parts -- Part two : Splitting. Splitting the universe : Decoherence and parallel worlds -- Order and randomness : Where probability comes from -- Does this ontological commitment make me look fat? : A Socratic dialogue on quantum puzzles -- Other ways : Alternatives to many-worlds -- The human side : Living and thinking in a quantum universe -- Part three : Spacetime. Why is there space? : Emergence and locality -- A world of vibrations : Quantum field theory -- Breathing in empty space : Finding gravity within quantum mechanics -- Beyond space and time : Holography, black holes, and the limits of locality -- Epilogue : Everything is quantum.
Includes bibliographical references (pages 329-335) and index.
CSE
Development Book Agency
Keywords: Quantum theory; Space and time; Quantum field theory; Wave functions; Space and time; Computer science; SCIENCE / Physics / Quantum Theory; SCIENCE / Gravity; Quantum theory; Space and time